Positive electrode composite material, method for manufacturing positive electrode composite material, and lithium ion battery

By adopting a two-stage mixing process in the manufacturing process of the positive electrode composite of lithium-ion battery, the problem of insufficient magnification characteristics in the prior art is solved, and excellent magnification characteristics and efficient Li+ conductivity are achieved.

CN119631191APending Publication Date: 2025-03-14IDEMITSU KOSAN CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380054944.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-07
Filing Date
2023-08-23
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art has shortcomings in improving the magnification characteristics of the positive electrode composite materials of lithium-ion batteries, especially in maintaining the crystallinity of the solid electrolyte and achieving a good mixing state between the sulfur-carbon composite and the solid electrolyte.

Method used

In the manufacturing process of the positive electrode composite, a two-stage mixing process is adopted: a solid electrolyte is added to the sulfur-based active substance in the first mixing process and a mixing process is performed, and a solid electrolyte is further added to the first mixture in the second mixing process and a mixing process is performed at a smaller energy than the first mixing process in the second mixing process to maintain the crystallinity of the solid electrolyte.

Benefits of technology

The excellent magnification characteristics of the positive electrode composite material are achieved, and the Li+ conductivity and overall performance of the battery are improved by taking into account the good mixing state and crystallinity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005249586590000161
    Figure BDA0005249586590000161
  • Figure BDA0005249586590000171
    Figure BDA0005249586590000171
  • Figure BDA0005249586590000191
    Figure BDA0005249586590000191
Patent Text Reader

Abstract

A positive electrode composite material containing a conductive auxiliary agent as a carbon material, a sulfur-based active material, and a solid electrolyte, the positive electrode composite material having a mapping overlap ratio of carbon and phosphorus of 50% or more in elemental analysis by energy dispersive X-ray spectroscopy using an electron microscope image, and having an overlap ratio of carbon and phosphorus of 50% or more in powder X-ray diffraction using CuK [alpha] rays. A diffraction peak A exists at 2theta = 20.2 + / -0.5 degrees, and a diffraction peak B exists at 2theta = 41.1 + / -0.8 degrees.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a positive electrode composite material, a method for producing the positive electrode composite material and a lithium ion battery.

[0002] Specifically, the present invention relates to a positive electrode composite material capable of exhibiting excellent rate characteristics, a method for producing the positive electrode composite material, and a lithium ion battery. Background Art

[0003] In a sulfur-based positive electrode composite material used in lithium-ion batteries and the like, sulfur is composited with a conductive additive and a solid electrolyte (SE), so that an insulating sulfur reaction can be sufficiently caused (Patent Document 1).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2013-258079 Summary of the invention

[0007] However, from the viewpoint of further improving rate characteristics, it has been found that the prior art including Patent Document 1 has room for further improvement.

[0008] An object of the present invention is to provide a positive electrode composite material capable of exhibiting excellent rate characteristics, a method for producing the positive electrode composite material, and a lithium ion battery.

[0009] As a result of intensive research, the present inventors have found that a positive electrode composite material satisfying specific conditions can exhibit excellent rate characteristics, thereby completing the present invention.

[0010] According to the present invention, the following positive electrode composite material and the like can be provided.

[0011] 1. A positive electrode composite material comprising a conductive additive as a carbon material, a sulfur-based active material, and a solid electrolyte,

[0012] In the elemental analysis using energy dispersive X-ray spectroscopy of electron microscope images, the overlap rate of carbon and phosphorus mapping is more than 50%.

[0013] In powder X-ray diffraction using CuKα rays, the compound had a diffraction peak A at 2θ=20.2±0.5° and a diffraction peak B at 2θ=41.1±0.8°.

[0014] 2. The positive electrode composite material as described in 1, wherein the half width of the diffraction peak B is 1.15° or less.

[0015] 3. The positive electrode composite material according to 1 or 2, wherein the solid electrolyte contains lithium atoms, phosphorus atoms, sulfur atoms, bromine atoms and iodine atoms.

[0016] 4. The positive electrode composite material according to any one of 1 to 3, wherein the weight reduction rate when heat-treated at 190° C. for 2 hours is 2.5% or more.

[0017] 5. The positive electrode composite material according to any one of 1 to 4, wherein the weight reduction rate of the sulfur-based active material when heat-treated at 190° C. for 2 hours is 7.0% or more.

[0018] 6. The positive electrode composite material as described in any one of items 1 to 5 is obtained by a manufacturing method including a first mixing step and a second mixing step, wherein the first mixing step is to obtain a first mixture by adding a solid electrolyte to a sulfur-based active material and mixing the mixture, and the second mixing step is to obtain a second mixture by further adding a solid electrolyte to the first mixture and mixing the mixture, and the mixing process is performed in the second mixing step with less energy than that in the first mixing step.

[0019] 7. The positive electrode composite material as described in 6,

[0020] The first mixing step is to perform mixing treatment under conditions that promote amorphization of the solid electrolyte added in the first mixing step;

[0021] The second mixing step is performed under the condition that the crystallinity of the solid electrolyte added in the second mixing step does not disappear.

[0022] 8. A method for manufacturing a positive electrode composite material, comprising:

[0023] a first mixing step of adding a solid electrolyte to a sulfur-based active material and mixing the mixture to obtain a first mixture; and

[0024] a second mixing step of further adding a solid electrolyte to the first mixture and mixing the mixture to obtain a second mixture;

[0025] In the second mixing step, mixing is performed with less energy than in the first mixing step.

[0026] 9. The method for producing the positive electrode composite material as described in 8,

[0027] The first mixing step is to perform mixing treatment under conditions that promote amorphization of the solid electrolyte added in the first mixing step;

[0028] The second mixing step is performed under the condition that the crystallinity of the solid electrolyte added in the second mixing step does not disappear.

[0029] 10. The method for producing a cathode composite material according to 8 or 9, which produces the cathode composite material according to any one of 1 to 7.

[0030] 11. A lithium ion battery comprising the positive electrode composite material according to any one of 1 to 7.

[0031] According to the present invention, a positive electrode composite material capable of exhibiting excellent rate characteristics, a method for producing the positive electrode composite material, and a lithium ion battery can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is a diagram showing the results of energy dispersive X-ray spectroscopy (SEM-EDS analysis) of the electron microscope image of Example 1 (in Figure 1 And the following Figure 2 to Figure 9 In the figure, (a) represents the image before processing, and (b) represents the image after processing. In addition, C represents the mapping of carbon, and P represents the mapping of phosphorus. ).

[0033] Figure 2 This is a diagram showing the results of SEM-EDS analysis of Example 2.

[0034] Figure 3 It is a figure which shows the result of SEM-EDS analysis of Comparative Example 1.

[0035] Figure 4 It is a figure which shows the result of SEM-EDS analysis of Comparative Example 2.

[0036] Figure 5 It is a figure which shows the result of SEM-EDS analysis of Example 3.

[0037] Figure 6 It is a figure which shows the result of SEM-EDS analysis of Example 4.

[0038] Figure 7 It is a figure which shows the result of SEM-EDS analysis of Example 5.

[0039] Figure 8 It is a figure which shows the result of SEM-EDS analysis of Example 6.

[0040] Fig. 9 It is a figure which shows the result of SEM-EDS analysis of Example 7.

[0041] Fig.10 It is a graph showing the results of powder X-ray diffraction (XRD) of Examples 1 and 2, Comparative Examples 1 and 2, and Reference Example 1.

[0042] Fig.11 It is a graph showing the XRD results of Example 3 and Example 4.

[0043] Fig.12 It is a graph showing the XRD results of Example 5, Example 6 and Comparative Example 3.

[0044] Fig.13 It is a graph showing the XRD results of Example 7 and Comparative Example 4. DETAILED DESCRIPTION

[0045] Hereinafter, the cathode composite material, the method for producing the cathode composite material, and the lithium ion battery of the present invention will be described in detail.

[0046] In addition, in this specification, "x to y" is a numerical range indicating "x or more and y or less." Regarding the numerical range, the upper limit value and the lower limit value described can be arbitrarily combined.

[0047] 1. Positive electrode composite materials

[0048] A positive electrode composite material of one embodiment of the present invention comprises a conductive aid as a carbon material, a sulfur-based active material, and a solid electrolyte. In the elemental analysis performed by energy dispersive X-ray spectroscopy using electron microscope images, the overlap rate of the mapping of carbon and phosphorus is more than 50%, and in the powder X-ray diffraction using CuKα rays, it has a diffraction peak A at 2θ=20.2±0.5° and a diffraction peak B at 2θ=41.1±0.8°.

[0049] According to the positive electrode composite material of this embodiment, it is possible to obtain an effect of being able to exhibit excellent rate characteristics.

[0050] The overlap ratio is a value measured based on the mapping of carbon and phosphorus after smoothing, compression and binarization, and is specifically a value measured by the method described in the Examples. In addition, powder X-ray diffraction is also measured according to the method described in the Examples.

[0051] In the positive electrode composite material of this embodiment, the sulfur-based active material and the solid electrolyte are well mixed, as determined by the above overlap ratio. In addition, as determined by the above diffraction peaks, the crystallinity of the solid electrolyte is well maintained, so Li + As a result, excellent rate characteristics are exhibited.

[0052] The positive electrode composite material of this proposal cannot be produced by existing technology.

[0053] That is, when a method of adding a solid electrolyte to a sulfur-carbon complex and applying strong energy to mechanically mix the solid electrolyte is used, the crystallinity of the solid electrolyte is reduced due to the mechanical mixing, and Li + The electrical conductivity is reduced, so the improvement of the rate characteristics of the positive electrode composite material is limited.

[0054] Furthermore, when the positive electrode composite material is produced by mechanical mixing with relatively weak energy as in the technology of Patent Document 1, the reduction in the crystallinity of the solid electrolyte is suppressed. Instead, a good mixing state of the sulfur-carbon composite and the solid electrolyte cannot be obtained, making it more difficult to improve the rate characteristics.

[0055] In one embodiment, the overlap ratio is preferably 50% or more, more preferably 55% or more, and particularly preferably 57% or more. The upper limit is not particularly limited and may be 100%, for example, 90% or less or 80% or less.

[0056] In this embodiment, the positive electrode composite material has a diffraction peak A at 2θ=20.2±0.5° and a diffraction peak B at 2θ=41.1±0.8° in powder X-ray diffraction using CuKα rays. Diffraction peaks A and B originate from crystals contained in the solid electrolyte.

[0057] In one embodiment, the positive electrode composite material may further have a diffraction peak at 2θ=23.6±0.5°.

[0058] In one embodiment, the half width of the diffraction peak B is 1.15° or less. + The electrical conductivity is further improved, and the rate characteristics are further improved.

[0059] The half width of the diffraction peak B is a value obtained by subtracting a device constant, and is specifically calculated by the method described in Examples.

[0060] A solid electrolyte with good crystallinity (a solid electrolyte with a narrow half width of diffraction peak B) is used as a raw material, and when manufacturing the positive electrode composite material, it is mixed in a manner that does not reduce its crystallinity as much as possible, thereby enabling the half width of diffraction peak B to be 1.15° or less. In the case where the crystallinity of the solid electrolyte is excessively destroyed during mixing, even if recrystallization is attempted by subsequent heating, the half width of diffraction peak B cannot be less than 1.15°.

[0061] The sulfur-based active material is not particularly limited, and examples thereof include sulfur, lithium sulfide (Li2S), lithium polysulfide (Li2S n: n satisfies 1<n≤8), titanium sulfide (TiS2), molybdenum sulfide (MoS2), iron sulfide (FeS, FeS2), copper sulfide (CuS), nickel sulfide (Ni3S2), sulfur-containing polymer compounds, etc.

[0062] The sulfur is not particularly limited, but is preferably high-purity sulfur. Specifically, the purity is preferably 95% by mass or more, more preferably 96% by mass or more, and particularly preferably 97% by mass or more.

[0063] Examples of the crystal system of sulfur include α sulfur (orthorhombic system), β (monoclinic system), γ (monoclinic system), and amorphous sulfur, etc. These may be used alone or in combination of two or more.

[0064] The solid electrolyte contains a sulfide crystallized lithium superion conductor region type II crystal structure. As a result, the above-mentioned diffraction peaks A and B are observed. Here, "sulfide crystallized lithium superion conductor region type II crystal structure" means Li 4-x Ge 1-x P x The S4 type sulfide crystalline lithium superion conductor region II (thio-LISICON Region II) type crystal structure (see Kanno et al., Journal of The Electrochemical Society, 148 (7) A742-746 (2001)), and Li 4-x Ge 1-x P x Any one of the S4-type sulfide crystalline lithium superion conductor region II (thio-LISICON Region II) type similar crystal structures (see Solid State Ionics, 177 (2006), 2721-2725).

[0065] In addition, the solid electrolyte may be a solid electrolyte having the above-mentioned sulfide crystallized lithium superion conductor region type II crystal structure, or may be a solid electrolyte having the above-mentioned sulfide crystallized lithium superion conductor region type II crystal structure as a main crystal. From the viewpoint of obtaining higher ion conductivity, it is preferred to have it as a main crystal. In this specification, "having it as a main crystal" means that the proportion of the target crystal structure in the crystal structure is 80% or more, preferably 90% or more, and more preferably 95% or more.

[0066] In one embodiment, the solid electrolyte contains lithium atoms, phosphorus atoms, sulfur atoms, bromine atoms, and iodine atoms, thereby further improving ion conductivity and rate characteristics.

[0067] In this embodiment, the mixing ratio (molar ratio) of lithium atoms, sulfur atoms, phosphorus atoms, bromine atoms and iodine atoms is not particularly limited, and is preferably 1.0-1.8: 1.0-2.0: 0.1-0.8: 0.01-0.3: 0.01-0.3, more preferably 1.1-1.7: 1.2-1.8: 0.2-0.6: 0.02-0.25: 0.02-0.25, more preferably 1.2-1.6: 1.3-1.7: 0.25-0.5: 0.03-0.2: 0.03-0.2, and further preferably 1.35-1.45: 1.4-1.7: 0.3-0.45: 0.04-0.18: 0.04-0.18.

[0068] As the conductive aid of the carbon material, any material having electronic conductivity can be used. The conductive aid preferably has a plurality of pores. A carbon material having pores is particularly preferred. The carbon material has high conductivity and is lighter than other conductive materials, so the output density and capacity per unit weight of the battery can be increased.

[0069] The specific surface area of ​​the conductive additive is preferably 0.1 m 2 / g above 5000m 2 / g or less, more preferably 1m 2 / g above 4000m 2 / g or less, more preferably 1m 2 / g above 3000m 2 / g or less, and most preferably 10m 2 / g above 3000m 2 / g or less.

[0070] The pore volume of the conductive auxiliary agent is preferably 0.1 cc / g to 5.0 cc / g.

[0071] The average diameter of the pores of the conductive auxiliary agent is preferably 0.1 nm to 40 nm, more preferably 0.5 nm to 40 nm, further preferably 0.5 nm to 20 nm, and most preferably 1 nm to 20 nm.

[0072] The specific surface area, pore volume, and pore diameter of the conductive aid can be obtained using a nitrogen adsorption isotherm obtained by adsorbing nitrogen gas on the conductive aid at liquid nitrogen temperature. Specifically, the specific surface area can be calculated using the nitrogen adsorption isotherm by the Brenauer-Emmet-Telle (BET) multipoint method. In addition, the pore volume and pore diameter can be obtained using the Barret-Joyner-Halenda (BJH) method using the nitrogen adsorption isotherm.

[0073] As a measuring device, for example, a specific surface area and pore size distribution measuring device (Autosorb-3) manufactured by Quantachrome Technologies Inc. can be used for measurement.

[0074] As carbon material, there is no particular limitation, and carbon blacks such as Ketjen black, acetylene black, superconductive acetylene black (DenkaBlack), thermal black, channel black, mesoporous carbon, activated carbon, amorphous carbon, carbon nanotubes, vapor grown carbon fiber (VGCF), carbon nanohorns, etc. can be exemplified, and as conductive carbon material, fullerene, carbon fiber, natural graphite, artificial graphite, graphene, graphene oxide, reduced graphene oxide, etc. can be exemplified. In addition, these can be used alone, or two or more can be used in combination. In addition, these composite materials can also be used.

[0075] Mesoporous carbon is a carbon material having two-dimensional or three-dimensional pores, which can be obtained by the preparation methods described in the following literature: for example, S. J. Song, S. H. Joo, R. Ryoo, etc., J. Am. Chem. Soc. (Journal of the American Chemical Society), 122 (2000) 10712-10713, and T. Yokoi, Y. Sakamoto, O. Terasaki, etc., J. Am. Chem. Soc. (Journal of the American Chemical Society), 128 (2006) 13664-13665.

[0076] In one embodiment, the positive electrode composite material may or may not contain other components besides the sulfur-based active material, the solid electrolyte and the conductive additive.

[0077] The other components are not particularly limited, and examples thereof include a binder, a solvent, and a dispersant.

[0078] In the positive electrode composite material, the contents of the sulfur-based active material, the solid electrolyte, and the conductive aid are not particularly limited.

[0079] In one embodiment, the content of the sulfur-based active material is 40 to 350 parts by mass based on 100 parts by mass of the solid electrolyte.

[0080] In one embodiment, the content of the conductive auxiliary agent is 10 to 300 parts by mass based on 100 parts by mass of the solid electrolyte.

[0081] In one embodiment, 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 99% by mass or more, 99.5% by mass or more, or substantially 100% by mass of the positive electrode composite material is a conductive additive, a sulfur-based active material, and a solid electrolyte. In addition, in the case of "substantially 100% by mass", unavoidable impurities may also be included.

[0082] In one embodiment, when heat-treated at 190° C. for 2 hours, the weight reduction rate of the positive electrode composite material is 2.5% or more, preferably 3.0% or more, and more preferably 3.5% or more.

[0083] In one embodiment, when heat-treated at 190° C. for 2 hours, the weight reduction rate of the sulfur-based active material of the positive electrode composite material is 7.0% or more, preferably 9.0% or more, and more preferably 11.0% or more.

[0084] By fully pulverizing the conductive aid as a carbon material, the sulfur filled in the pores of the carbon is easily released by heating, thereby producing a weight reduction rate (especially the weight reduction rate of the sulfur-based active material) when heated at 190°C for 2 hours. Therefore, it can be said that the higher the weight reduction rate (especially the weight reduction rate of the sulfur-based active material), the higher the dispersibility of each component in the positive electrode composite material. As a result, the positive electrode composite material can exert a more excellent rate characteristic.

[0085] The above-mentioned weight reduction rate and sulfur-based active material weight reduction rate are values ​​measured by the methods described in Examples.

[0086] 2. Method for manufacturing positive electrode composite material

[0087] A method for manufacturing a positive electrode composite material according to one embodiment of the present invention comprises: a first mixing step, in which a solid electrolyte is added to a sulfur-based active material and mixed to obtain a first mixture; and a second mixing step, in which a solid electrolyte is further added to the first mixture and mixed to obtain a second mixture, wherein the mixing is performed with less energy than that in the first mixing step.

[0088] According to the method for producing a cathode composite material of this embodiment, a cathode composite material capable of exhibiting excellent rate characteristics can be obtained.

[0089] That is, the sulfur-based active material and the solid electrolyte can be fully mixed in the first mixing step, and in the second mixing step, the crystallinity of the solid electrolyte can be appropriately maintained by performing the mixing process with less energy than in the first mixing step. As a result, a good mixing state and crystallinity can be achieved, and the rate characteristics can be improved.

[0090] In this embodiment, the description of the above-mentioned positive electrode composite material can be applied to the conductive auxiliary agent and the sulfur-based active material.

[0091] The solid electrolyte added in the first mixing step and the solid electrolyte added in the second mixing step may be the same or different. In addition, the solid electrolyte added in the first mixing step may be used alone or in combination of two or more. Furthermore, the solid electrolyte added in the second mixing step may be used alone or in combination of two or more.

[0092] The solid electrolyte used in the first mixing step is not particularly limited, and for example, a sulfide solid electrolyte may be mentioned.

[0093] The sulfide solid electrolyte is a solid electrolyte that contains at least sulfur atoms and exhibits ionic conductivity caused by the metal atoms contained therein; it is a solid electrolyte that preferably contains lithium atoms and phosphorus atoms in addition to sulfur atoms, and more preferably contains lithium atoms, phosphorus atoms and halogen atoms, and has ionic conductivity caused by lithium atoms.

[0094] In one embodiment, the solid electrolyte includes lithium atoms, phosphorus atoms, sulfur atoms, bromine atoms, and iodine atoms.

[0095] The sulfide solid electrolyte may be an amorphous sulfide solid electrolyte or a crystalline sulfide solid electrolyte.

[0096] (Amorphous sulfide solid electrolyte)

[0097] As an amorphous sulfide solid electrolyte, any amorphous sulfide solid electrolyte can be used without particular limitation as long as it contains at least sulfur atoms and exhibits ionic conductivity caused by the metal atoms contained therein. As representative amorphous sulfide solid electrolytes, for example, solid electrolytes containing sulfur atoms, lithium atoms and phosphorus atoms, such as Li2S-P2S5, which are composed of lithium sulfide and phosphorus sulfide; solid electrolytes composed of lithium sulfide, phosphorus sulfide and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr, etc.; solid electrolytes such as Li2S-P2S5-Li2O-LiI, Li2S-SiS2-P2S5-LiI, which also contain other elements such as oxygen and silicon. From the viewpoint of obtaining higher ion conductivity, solid electrolytes composed of lithium sulfide, phosphorus sulfide and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, and Li2S-P2S5-LiI-LiBr, are preferred.

[0098] The types of elements constituting the amorphous sulfide solid electrolyte can be confirmed by, for example, an ICP emission spectrometer.

[0099] When the amorphous sulfide solid electrolyte has at least Li2S-P2S5, the molar ratio of Li2S to P2S5 is preferably 30-85:15-70, more preferably 40-80:20-60, and further preferably 45-78:22-55, from the viewpoint of high chemical stability and higher ion conductivity.

[0100] For example, when the amorphous sulfide solid electrolyte is Li2S-P2S5-LiI-LiBr, the total content of lithium sulfide and phosphorus pentasulfide is preferably 30 to 95 mol%, more preferably 35 to 90 mol%, and further preferably 40 to 85 mol%. In addition, the ratio of lithium bromide to the total of lithium bromide and lithium iodide is preferably 1 to 99 mol%, more preferably 20 to 90 mol%, further preferably 40 to 80 mol%, and particularly preferably 50 to 70 mol%.

[0101] The shape of the amorphous sulfide solid electrolyte is not particularly limited, and may be, for example, a particle shape. The average particle size (D 50 ) For example, the range of 0.01 μm to 500 μm and 0.1 to 200 μm can be exemplified.

[0102] In this specification, the average particle size (D 50 ) is the particle size when the cumulative particle size distribution curve is drawn, starting from the smallest particle and accumulating to reach 50% of the total. The volume distribution is, for example, the average particle size that can be measured using a laser diffraction / scattering particle size distribution measuring device.

[0103] (Crystalline sulfide solid electrolyte)

[0104] As the crystalline sulfide solid electrolyte, for example, so-called glass ceramics obtained by heating the above-mentioned amorphous sulfide solid electrolyte to a crystallization temperature or higher may be used. A sulfide solid electrolyte having the following crystal structure can be used.

[0105] Examples of the crystal structure that a crystalline sulfide solid electrolyte containing lithium atoms, sulfur atoms, and phosphorus atoms may have include Li3PS4 crystal structure, Li4P2S6 crystal structure, Li7PS6 crystal structure, Li7P3S 11 A crystal structure, a crystal structure having peaks near 2θ=20.2° and 23.6° (for example, Japanese Patent Application Laid-Open No. 2013-16423), and the like.

[0106] In addition, examples of the crystal structure that the crystalline sulfide solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms may have include the above-mentioned Li 4-x Ge 1-x Px S4-type sulfide crystalline lithium superion conductor region II (thio-LISICON Region II) crystal structure, and Li 4-x Ge 1-x P x S4 type sulfide crystalline lithium superion conductor region II (thio-LISICON Region II) type similar crystal structure, etc.

[0107] In the X-ray diffraction measurement using CuKα rays, the diffraction peaks of the Li3PS4 crystal structure appear, for example, at 2θ=17.5°, 18.3°, 26.1°, 27.3°, and 30.0°; the diffraction peaks of the Li4P2S6 crystal structure appear, for example, at 2θ=16.9°, 27.1°, and 32.5°; the diffraction peaks of the Li7PS6 crystal structure appear, for example, at 2θ=15.3°, 25.2°, 29.6°, and 31.0°; and the diffraction peaks of the Li7P3S 11 The diffraction peaks of the crystal structure appear near 2θ=17.8°, 18.5°, 19.7°, 21.8°, 23.7°, 25.9°, 29.6°, and 30.0°, for example. 4-x Ge 1-x P x The diffraction peaks of the S4-type sulfide crystalline lithium superion conductor region II (thio-LISI CON Region II) crystal structure appear near 2θ=20.1°, 23.9°, and 29.5°, which are similar to Li 4-x Ge 1-x P x The diffraction peaks of the S4 type thio-LISICON Region II-type crystal structure appear near 2θ=20.2° and 23.6°, for example. These peak positions may fluctuate within a range of ±0.5°.

[0108] In addition, as the crystal structure of the crystalline sulfide solid electrolyte, the argyrodite type crystal structure can also be cited. As the argyrodite type crystal structure, for example, the Li7PS6 crystal structure can be cited; the Li7PS6 structure skeleton having the composition formula Li 7-x P 1-y Si y S6 and Li 7+x P 1-y Si y The crystal structure represented by S6 (x is -0.6 to 0.6, y is 0.1 to 0.6); 7-x-2y PS 6-x-y Cl xThe crystal structure represented by (0.8≤x≤1.7, 0<y≤-0.25x+0.5); 7-x PS 6-x Ha x (Ha is Cl or Br, and x is preferably 0.2 to 1.8)

[0109] Among the above-mentioned crystal structures, the crystal structure possessed by the crystalline sulfide solid electrolyte is preferably a Li3PS4 crystal structure, a sulfide crystalline lithium superion conductor region type II crystal structure, or an argyrodite-type crystal structure.

[0110] The shape of the crystalline sulfide solid electrolyte is not particularly limited, and may be, for example, a particle shape. The average particle size (D 50 ) and the average particle size (D 50 ) Similarly, for example, it can be exemplified within the range of 0.01 μm to 500 μm and 0.1 to 200 μm.

[0111] The mixing amount of the solid electrolyte used in the first mixing step is preferably 1 to 80% of the total mass of the solid electrolyte added in the first mixing step and the second mixing step, and more preferably 5 to 75%.

[0112] As described above, the solid electrolyte used in the second mixing step contains the sulfide crystalline lithium superion conductor region type II crystal structure.

[0113] The mixing amount of the solid electrolyte used in the second mixing step is preferably 20 to 99% of the total mass of the solid electrolyte added in the first mixing step and the second mixing step, and more preferably 25 to 95%.

[0114] The ratio of the total mass of the solid electrolyte added in the first mixing step and the second mixing step to the total mass of the sulfur-based active material and the conductive additive (solid electrolyte: sulfur-based active material + conductive additive) is 10:90 to 90:10, preferably 15 to 70:85 to 30, and more preferably 20 to 60:80 to 40.

[0115] In one embodiment, when a crystalline solid electrolyte is used in the first mixing step, the first mixing step is performed under conditions that promote amorphization of the solid electrolyte added in the first mixing step; and the second mixing step is performed under conditions that do not eliminate the crystallinity of the solid electrolyte added in the second mixing step. Thus, the rate characteristics can be further improved.

[0116] In addition, the advancement of amorphization can be judged by the broadening of the peak derived from the crystal component in X-ray diffraction measurement.

[0117] The energy of the mixing treatment in each of the first mixing step and the second mixing step is not particularly limited as long as the condition of the first mixing step > the second mixing step is satisfied. For example, in the first mixing step, the mixing treatment can be carried out under the following conditions: a weakening of the intensity of the crystal peak of the solid electrolyte added in the first mixing step, an increase in the peak half-width, or the disappearance of the peak can occur. On the other hand, in the second mixing step, the mixing treatment can be carried out under the condition that the crystal peak of the solid electrolyte added in the second mixing step does not disappear, and preferably, the mixing treatment can be carried out under the condition that the change in the intensity of the crystal peak or the change in the peak half-width is small. Here, "small change" means, for example, that the rate of change can be smaller than the rate of change in the first mixing step.

[0118] Examples of the mixing device used in the first mixing step include a planetary ball mill, a tumbling mill, a bead mill, FILMIX (thin film gyratory high-speed mixer), a NAUTA mixer (conical screw mixer), a cyclone mixer, a twin-shaft extruder, a multi-shaft roll, and a solid phase shear kneader.

[0119] As the mixing device used in the second mixing step, the device exemplified in the first mixing step can be used. However, when selecting the mixing device or setting the operating conditions, the energy of the mixing process satisfies the condition of the first mixing step > the second mixing step. The devices used in the first mixing step and the second mixing step may be the same or different. When the same device is used, for example, a method of setting the processing time or accumulated power to the first mixing step > the second mixing step; or if it is a device that uses rotational power such as a planetary ball mill or a rolling mill, a method of setting the rotation speed to the first mixing step > the second mixing step, etc. can be used.

[0120] In one embodiment, a planetary ball mill is used in the first mixing step.

[0121] In one embodiment, a tumbling mill is used in the second mixing step.

[0122] In one embodiment, the sulfur-based active material to be used in the first mixing step is previously composited with a conductive auxiliary agent.

[0123] For example, before the first mixing step, the sulfur-based active material and the conductive auxiliary agent can be composited by heating them together. The heating temperature is not particularly limited, and is, for example, a temperature exceeding 120° C., for example, 150° C. or higher, 170° C. or higher, 200° C. or higher, 150° C. or higher, 200° C. or higher, 250° C. or higher, or 300° C. or higher. The upper limit is, for example, 350° C. or lower.

[0124] The mass ratio of the sulfur-based active material to the conductive aid (sulfur-based active material:conductive aid) is 10:90 to 95:5, preferably 20 to 80:90 to 10.

[0125] In one embodiment, the positive electrode composite material produced by the method for producing a positive electrode composite material according to this embodiment is the positive electrode composite material according to one embodiment of the present invention described above.

[0126] 3. Lithium-ion battery

[0127] A lithium ion battery according to one embodiment of the present invention includes the positive electrode composite material according to one embodiment of the present invention described above.

[0128] According to the lithium ion battery of this embodiment, it is possible to obtain an effect of being able to exhibit excellent rate characteristics.

[0129] The positive electrode composite material can be used as a positive electrode layer of a lithium ion battery. In this case, other structures of the lithium ion battery can use structures known in the technical field, and a negative electrode layer containing no lithium ions in the negative electrode active material can be selected.

[0130] In addition, the negative electrode active material contained in the negative electrode layer of the lithium ion battery can be referred to as “negative electrode active material containing lithium ions”. In addition, the negative electrode active material contained in the negative electrode layer of the lithium ion battery can also be “negative electrode active material that supplies lithium ions to the positive electrode”.

[0131] The negative electrode of the lithium ion battery is not particularly limited as long as it can be used in a common battery. The negative electrode may be composed of a negative electrode mixture obtained by mixing a negative electrode active material and a solid electrolyte.

[0132] As the negative electrode active material, commercially available materials can be used. For example, carbon materials, Sn metal, In metal, Si metal, alloys of these metals, etc. can be used. Specifically, natural graphite or various graphites; metal powders of Si, Sn, Al, Sb, Zn, Bi, etc.; metal alloys such as SiAl, Sn5Cu6, Sn2Co, Sn2Fe; other amorphous alloys or plated alloys. There is no particular limitation on the particle size, and materials with an average particle size of several μm to 80 μm can be suitably used.

[0133] The electrolyte layer is not particularly limited, and a known electrolyte layer can be used. For example, preferably an oxide solid electrolyte, a sulfide solid electrolyte, a polymer electrolyte, and from the viewpoint of ionic conductivity, more preferably a sulfide solid electrolyte. The sulfide solid electrolyte is preferably an electrolyte for the above-mentioned cathode composite material.

[0134] The method for manufacturing a lithium-ion battery is not particularly limited. For example, the following method can be cited: a positive electrode layer composed of a positive electrode composite material according to one embodiment of the present invention is formed on a positive electrode collector to form a sheet, a solid electrolyte layer is formed on the sheet, and a sheet having a negative electrode layer formed on a negative electrode collector is stacked and pressed.

[0135] Example

[0136] Examples of the present invention will be described below, but the present invention is not limited to these examples.

[0137] (Example 1)

[0138] 1. Preparation of positive electrode composite materials

[0139] (1) Preparation of composite powder A

[0140] Activated carbon (MSC-30 manufactured by Kansai Thermochemical Co., Ltd.) and sulfur were placed in a glass bottle at a mass ratio of 3:7, sealed in a SUS tube container, and heated in an electric furnace at 150°C for 6 hours and at 300°C for 2.75 hours to obtain a composite powder A of activated carbon and sulfur.

[0141] (2) Preparation of Solid Electrolyte A

[0142] 0.4127g of lithium sulfide, 0.6655g of phosphorus pentasulfide, 0.2137g of lithium iodide, 0.2080g of lithium bromide, and 10 zirconia balls with a diameter of 10mm were put into a 45mL zirconia can and sealed. A planetary ball mill (manufactured by FRITSCH, model P-7) was used to mix (mechanically grind) at a speed of 370rpm for 40 hours to obtain a powder. The obtained powder was heated at 195°C for 3 hours to obtain a solid electrolyte A.

[0143] (3) Preparation of positive electrode composite material powder

[0144] 1st Mixing Step

[0145] 0.9 g of composite powder A and 0.18 g of solid electrolyte A were put into a 45 mL zirconia can together with 10 zirconia balls with a diameter of 10 mm, and sealed. A planetary ball mill (Fritsch, model P-7) was used to mix at a speed of 370 rpm at room temperature for 20 hours to obtain composite powder B.

[0146] Second mixing step

[0147] 0.54 g of composite powder B and 0.36 g of solid electrolyte A were put into a 45 mL zirconia can together with 34 g of zirconia balls with a diameter of 2 mm, and sealed. A rolling mill ("small ball mill stand", Asahi Rika Manufacturing Co., Ltd., model AV-1) was used to mix at a speed of 600 rpm for 1 hour at room temperature to obtain a positive electrode composite material powder.

[0148] 2. Measurement methods and test methods

[0149] (1) Energy dispersive X-ray spectroscopy (SEM-EDS analysis) of electron microscope images and calculation of the overlap ratio of carbon and phosphorus

[0150] Preparation of positive electrode composite particles

[0151] 100 mg of solid electrolyte A was put into a cylinder made of MACOR (glass ceramic) with a diameter of 10 mm and pressurized. 20 mg of the obtained positive electrode composite material powder was put into the pressurized surface and pressurized again. Then 20 mg of positive electrode composite material powder was put into the pressurized surface on the opposite side and pressurized again, and the molded body was taken out from the cylinder to obtain positive electrode composite material particles.

[0152] SEM-EDS analysis

[0153] The positive electrode composite material particles are divided in the vertical direction, and the exposed surface is subjected to ion milling treatment (manufactured by Hitachi High-Technologies Corporation, IM4000), thereby exposing the cross section of the positive electrode composite material particles. SEM (manufactured by Hitachi High-Technologies Corporation, SU8220) and EDS (manufactured by Bruker, QUANTAX Flat QUAD) are used to perform SEM-EDS element mapping measurement on the obtained cross section to obtain secondary electron images of 10 fields of view and EDS images of carbon and phosphorus. It is implemented with an observation magnification of 5000 times, an acceleration voltage of 10kV, and a scanning area of ​​1024×768. No special image processing is performed on the EDS mapping, and an image mapping the actual measured intensity is used.

[0154] In addition, during the SEM-EDS element mapping measurement, the area after the cross-section processing by ion milling was divided into two equal parts, and then the two-divided area was divided into five equal parts, and the SEM-EDS element mapping was acquired at a 5000-fold observation magnification for the center of each of the ten divided areas.

[0155] Calculation of the overlap ratio of carbon and phosphorus

[0156] Regarding the processing of the images obtained by the above steps, OpenCV (4.5.1) (computer vision library) based on Python (3.9.9) language was used. All EDS images of 10 fields of view of carbon and phosphorus were smoothed twice, and the smoothing process used a bilateral filter with d=15, sigmaColor (standard deviation of the color domain)=64, and sigmaSpace (standard deviation of the spatial domain)=64. For the obtained image, the MaxPooling2D (2D maximum pooling) (pool_size (size of the pooling window)=3, strides (stride)=3) of the open source neural network library Keras (2.4.3) was used to compress the pixels to 1 / 3, and smoothed by a median filter. The smoothed image was grayed and binarized with a minimum brightness of 30 and a maximum brightness of 255 for carbon, and a minimum brightness of 40 and a maximum brightness of 255 for phosphorus.

[0157] The results of the SEM-EDS analysis including the above-mentioned image processing are shown in Figure 1 In addition, the results of Example 2 described later are shown in Figure 2 The results of Comparative Example 1 are shown in Figure 3 The results of Comparative Example 2 are shown in Figure 4 The results of Example 3 are shown in Figure 5 The results of Example 4 are shown in Figure 6 The results of Example 5 are shown in Figure 7 The results of Example 6 are shown in Figure 8 The results of Example 7 are shown in Fig. 9 .exist Figures 1 to 9 In the figure, (a) shows the image before processing (before smoothing, compression and binarization), and (b) shows the image after processing. In addition, C shows the mapping of carbon, and P shows the mapping of phosphorus.

[0158] By these processes, the image data is converted into a numerical matrix in which the element is 0 when it does not exist and 255 when it exists. In the numerical matrix of carbon and phosphorus, the overlap rate of one field of view is calculated by dividing the total number of pixels with 255 overlapping at the same coordinate by the total number of pixels. The average of the overlap rates of all 10 fields of view is taken as the overlap rate of this scheme.

[0159] (2) Powder X-ray Diffraction (XRD) of Positive Electrode Composite Material Powder

[0160] The obtained positive electrode composite material powder was subjected to XRD measurement.

[0161] Specifically, the positive electrode composite material powder was filled into a groove with a diameter of 20 mm and a depth of 0.2 mm, and flattened with glass to prepare a sample. The sample was sealed with a kapton film for XRD and measured in a manner that it was not in contact with air.

[0162] The XRD measurement was performed using a powder X-ray diffraction measuring apparatus D2 PHASER manufactured by Bruker Corporation under the following measurement conditions.

[0163] [Measurement conditions]

[0164] Tube voltage: 30kV

[0165] Tube current: 10mA

[0166] X-ray wavelength: Cu-Kα ray

[0167] Optical system: Concentration method

[0168] Slit composition: Soller slit 4° (same for incident and receiving sides), divergence slit 1mm, Kβ filter (Ni plate 0.5%), air scattering screen (3mm)

[0169] Detector: Semiconductor detector

[0170] Measuring range: 2θ = 10-60 degrees

[0171] Step width, scanning speed: 0.05deg, 0.05deg / sec

[0172] In addition, 0.45 g of the composite powder A and 0.45 g of the solid electrolyte A were weighed into an agate mortar and mixed in the mortar for 10 minutes to obtain a reference sample (Reference Example 1), which was also subjected to XRD measurement.

[0173] The results are shown in Fig.10 In addition, the results of Examples 3 and 4 described later are shown in Fig.11 The results of Example 5, Example 6 and Comparative Example 3 are shown in Fig.12 The results of Example 7 and Comparative Example 4 are shown in Fig.13 .

[0174] Based on these results, the presence or absence of the diffraction peak A at 2θ=20.2±0.5° and the diffraction peak B at 2θ=41.1±0.8° were confirmed. In addition, the half width of the diffraction peak B was determined by the following method.

[0175] Calculation of half width of diffraction peak B

[0176] The peak half width (β) of the positive electrode composite is calculated as β=wB by subtracting a device constant (B) inherent to the measuring device from the half width (w) obtained by the measurement.

[0177] w: half width of the peak (diffraction peak B) at 41.1°±0.8° obtained by measurement

[0178] B: Device constant (B = 0.1269° was obtained from the peak at 2θ = 28.4° by measuring the standard substance (silicon) in the same way)

[0179] w (the half width obtained by measurement) is obtained as follows. A straight line baseline is set on the peak shape obtained by XRD measurement, and the difference between the intensity of each point and the baseline is taken to form an XRD curve. The XRD curve is set to a formula consisting of a Lorentzian function L(x) and a Gaussian function G(x) (f(x) = (1-α) × L(x) + α × G(x)), and the parameters A (corrected peak intensity), w, x0 (2θ of the peak top) and α (ratio of the Lorentzian function) are determined by curve fitting.

[0180] [Number 1]

[0181]

[0182] In the curve fitting, the range of about ±1.0° from the peak is appropriately set as the fitting range. The error between the intensity of the fitting curve calculated by f(x) at each θ and the intensity of the XRD curve is taken, and the value obtained by adding the errors of the entire fitting range is minimized to perform fitting. The solver function (GRG nonlinear) of spreadsheet software (Excel, Microsoft) is used here.

[0183] (3) Weight reduction rate measurement test during heating

[0184] The following measurements were performed on the obtained positive electrode composite material powder.

[0185] First, weigh the aluminum foil pan (Tokyo Glass Instruments, volume 12mL). Take 0.2000g (error is less than ±0.0005g) of each positive electrode composite material powder in the weighed pan, and level the powder so that it is distributed as evenly as possible on the bottom of the pan. Place the aluminum foil pan on a heating plate (AS ONE, ND-1A) and double-cover it with two types of (φ50mm×15mm high, φ60mm×20mm high) stainless steel pans. In this state, heat it to 190°C and keep it constant for 2 hours to perform heat treatment.

[0186] After the heat treatment, the aluminum foil pan carrying the powder is weighed after gradually cooling. The total weight of the powder and the aluminum foil pan at this time is subtracted from the total weight measured before heating, thereby calculating the weight loss (ΔW) in the powder during the heat treatment. The ΔW is divided by the weight of the powder before the heat treatment and converted into a percentage to calculate the weight loss rate. In addition, the ΔW is divided by the weight of the sulfur-based active substance before the heat treatment and converted into a percentage to calculate the weight loss rate of the sulfur-based active substance. The weight of the sulfur-based active substance before the heat treatment is obtained by multiplying the weight of the powder before the heat treatment by the weight fraction of the sulfur-based active substance.

[0187] (4) Evaluation of battery characteristics

[0188] Fabrication of Lithium-ion Batteries (All-solid)

[0189] 100 mg of solid electrolyte A prepared by the above steps was pressure-formed in a cylinder made of MACOR (glass ceramic) with a diameter of 10 mm. The positive electrode composite material powder prepared above was put into the pressure surface in a manner that the amount of sulfur was 1.75 mg, and pressure-formed again. An all-solid-state battery was prepared by putting indium foil and lithium foil into the pressure surface opposite to the positive electrode composite material and pressurizing.

[0190] The obtained all-solid-state battery was subjected to a constant current charge and discharge test. The voltage range of the constant current charge and discharge test was set to 0.8-2.2 V, and the current value was set to the conditions in Table 1 below. As the discharge capacity (per sulfur mass) at 1C, the value of the 7th cycle under the following conditions was measured.

[0191] [Table 1]

[0192]

[0193] (Example 2)

[0194] 1st Mixing Step

[0195] 0.9 g of composite powder A obtained in the same manner as in Example 1 and 0.09 g of solid electrolyte A obtained in the same manner as in Example 1 were placed in a 45 mL zirconia can together with 10 zirconia balls having a diameter of 10 mm, and sealed. A planetary ball mill (manufactured by FRITSCH, model P-7) was used to mix at a rotation speed of 370 rpm at room temperature for 20 hours to obtain composite powder C.

[0196] Second mixing step

[0197] 0.495g of composite powder C and 0.405g of solid electrolyte A were put into a 45mL zirconia can together with 34g of zirconia balls with a diameter of 2mm, and sealed. A rolling mill ("small ball mill stand", Asahi Rika Manufacturing, model AV-1) was used to mix at a speed of 600rpm for 1 hour at room temperature to obtain a positive electrode composite material powder. The obtained positive electrode composite material powder was subjected to the same measurement and test as in Example 1.

[0198] (Comparative Example 1)

[0199] 0.45g of composite powder A obtained in the same manner as in Example 1 and 0.45g of solid electrolyte A obtained in the same manner as in Example 1 were put into a 45mL zirconia can together with 10 zirconia balls having a diameter of 10mm and sealed. Using a planetary ball mill device (manufactured by FRITSCH, model P-7), mixing was performed for 20 hours at room temperature at a speed of 370rpm to obtain a positive electrode composite material powder. The obtained positive electrode composite material powder was subjected to the same measurement and test as in Example 1.

[0200] (Comparative Example 2)

[0201] 0.45g of composite powder A obtained in the same manner as in Example 1 and 0.45g of solid electrolyte A obtained in the same manner as in Example 1 were put into a 45mL zirconia can together with 34g of zirconia balls having a diameter of 2mm and sealed. A rolling mill ("small ball mill stand", manufactured by Asahi Rika, model AV-1) was used to mix for 20 hours at a speed of 600rpm at room temperature to obtain a positive electrode composite material powder. The obtained positive electrode composite material powder was subjected to the same measurements and tests as in Example 1.

[0202] (Example 3)

[0203] 1st Mixing Step

[0204] The same procedure as in Example 1 was followed to obtain composite powder B.

[0205] Second mixing step

[0206] 0.54g of composite powder B and 0.36g of solid electrolyte A were put into a 45mL zirconia can together with 34g of zirconia balls with a diameter of 2mm, and sealed. A rolling mill ("small ball mill stand", Asahi Rika Manufacturing, model AV-1) was used to mix for 20 hours at a speed of 600rpm at room temperature to obtain a positive electrode composite material powder. The obtained positive electrode composite material powder was subjected to the same measurement and test as in Example 1.

[0207] (Example 4)

[0208] (1) Preparation of solid electrolyte B

[0209] 0.2058 g of lithium sulfide and 0.9942 g of phosphorus pentasulfide were placed in a 45 mL zirconia can together with 10 zirconia balls having a diameter of 10 mm, and the can was sealed. A planetary ball mill (manufactured by Fritsch, model P-7) was used to mix (mechanically grind) at a rotation speed of 370 rpm for 20 hours to obtain a powder.

[0210] (2) Preparation of positive electrode composite material powder

[0211] 1st Mixing Step

[0212] 0.9 g of composite powder A and 0.18 g of solid electrolyte B were put into a 45 mL zirconia can together with 10 zirconia balls with a diameter of 10 mm, and sealed. A planetary ball mill (Fritsch, model P-7) was used to mix at a speed of 370 rpm at room temperature for 20 hours to obtain composite powder D.

[0213] Second mixing step

[0214] 0.54g of composite powder D and 0.36g of solid electrolyte A were put into a 45mL zirconia can together with 34g of zirconia balls with a diameter of 2mm, and sealed. A rolling mill ("small ball mill stand", Asahi Rika Manufacturing, model AV-1) was used to mix at a speed of 600rpm for 1 hour at room temperature to obtain a positive electrode composite material powder. The obtained positive electrode composite material powder was subjected to the same measurement and test as in Example 1.

[0215] The above results are shown in Table 2. In addition, the battery characteristics, that is, the capacity obtained at each charge and discharge rate, are affected by the mass of the active material used (sulfur-based active material in the present technology), so it is appropriate to compare under the condition of consistent mass of the active material. The mass of active materials of Examples 1 to 4 and Comparative Examples 1 and 2 shown in Table 2 is consistent. Similarly, the mass of active materials of Examples 5, 6 and Comparative Example 3 shown in Table 4 are also consistent. In addition, similarly, the mass of active materials of Example 7 and Comparative Example 4 shown in Table 6 are also consistent.

[0216] [Table 2]

[0217]

[0218] (Example 5)

[0219] 1. Preparation of positive electrode composite materials

[0220] (1) Preparation of solid electrolyte C

[0221] Under a nitrogen atmosphere, 15.3g of lithium sulfide and 24.7g of phosphorus pentasulfide were put into a 1L reaction tank with a stirring blade. After the stirring blade was operated, 400mL of tetrahydrofuran cooled to -20°C was added to the container. After naturally warming to room temperature, stirring was continued for 72 hours, and the obtained reaction solution slurry was put into a glass filter (pore size: 40-100μm). After obtaining a solid component, the solid component was dried at 90°C to obtain Li3PS4 powder (purity: 90% by mass). Under a nitrogen atmosphere, 1.70g of the obtained Li3PS4 powder, 0.19g of lithium bromide, and 0.28g of lithium iodide were put into a Schlenk bottle with a stirrer (capacity: 100mL). After the stirrer was rotated, 20mL of tetramethylethylenediamine (TMEDA) as a complexing agent was added, stirring was continued for 12 hours, and the obtained electrolyte precursor containing material was dried under vacuum at room temperature to obtain a powder electrolyte precursor. The obtained electrolyte precursor was heated at 120° C. for 2 hours under vacuum, and further heated at 140° C. for 2 hours under vacuum, thereby obtaining a solid electrolyte C.

[0222] (2) Preparation of positive electrode composite material powder

[0223] 1st Mixing Step

[0224] 0.80 g of composite powder A and 0.20 g of solid electrolyte A were put into a 45 mL zirconia can together with 10 zirconia balls with a diameter of 10 mm, and sealed. A planetary ball mill (Fritsch, model P-7) was used to mix at a speed of 370 rpm at room temperature for 20 hours to obtain composite powder E.

[0225] Second mixing step

[0226] 0.675 g of composite powder E and 0.225 g of solid electrolyte C were put into a 45 mL zirconia can together with 34 g of zirconia balls with a diameter of 2 mm, and sealed. A rolling mill ("small ball mill stand", Asahi Rika Manufacturing Co., Ltd., model AV-1) was used to mix at a speed of 600 rpm for 1 hour at room temperature to obtain a positive electrode composite material powder.

[0227] 2. Measurement methods and test methods

[0228] (1) Energy dispersive X-ray spectroscopy (SEM-EDS analysis) of electron microscope images and calculation of the overlap ratio of carbon and phosphorus

[0229] SEM-EDS analysis was performed in the same manner as in Example 1, and the overlap ratio was calculated.

[0230] (2) Powder X-ray Diffraction (XRD) of Positive Electrode Composite Material Powder

[0231] XRD measurement was carried out in the same manner as in Example 1, and the half width of the diffraction peak B was calculated.

[0232] (3) Weight reduction rate measurement test during heating

[0233] The same test as in Example 1 was carried out.

[0234] (4) Evaluation of battery characteristics

[0235] Preparation of negative electrode composite materials

[0236] LTO ("LT-112" manufactured by Ishihara Sangyo) and a conductive aid ("Li-100" manufactured by Denka, acetylene black powder) were mixed in a mortar for 5 minutes with a Li2S-P2S5-LiCl-LiBr type solid electrolyte D at a mass ratio of 60:5:35 to obtain an LTO negative electrode composite material.

[0237] Fabrication of Lithium-ion Batteries (All-solid)

[0238] 100 mg of solid electrolyte A prepared by the above steps was pressurized in a cylinder made of MACOR (glass ceramic) with a diameter of 10 mm. The positive electrode composite material powder prepared above was put into the pressurized surface in a manner of 5.04 mg of sulfur, and pressurized again. 166 mg of LTO negative electrode composite material was put into the pressurized surface opposite to the positive electrode composite material and pressurized. A Li foil with a diameter of 9 mm and a thickness of 0.1 mm was put on it and pressurized again to make a full solid battery.

[0239] The obtained all-solid-state battery was subjected to a constant current charge and discharge test. The voltage range of the constant current charge and discharge test was set to -0.4 to +1.3 V, and the current value was set to the conditions in Table 3 below. As the discharge capacity (per sulfur mass) at 0.5 C, the value of the 7th cycle under the following conditions was measured.

[0240] [Table 3]

[0241]

[0242] (Example 6)

[0243] 1st Mixing Step

[0244] 0.75 g of composite powder A and 0.25 g of solid electrolyte A were put into a 45 mL zirconia can together with 10 zirconia balls with a diameter of 10 mm, and sealed. A planetary ball mill (Fritsch, model P-7) was used to mix at a speed of 370 rpm at room temperature for 20 hours to obtain composite powder F.

[0245] Second mixing step

[0246] 0.72g of composite powder F and 0.18g of solid electrolyte C were put into a 45mL zirconia can together with 34g of zirconia balls with a diameter of 2mm, and sealed. A rolling mill ("small ball mill stand", Asahi Rika Manufacturing, model AV-1) was used to mix at a speed of 600rpm for 1 hour at room temperature to obtain a positive electrode composite material powder. The obtained positive electrode composite material powder was subjected to the same measurement and test as in Example 5.

[0247] (Comparative Example 3)

[0248] 0.54g of composite powder A obtained in the same manner as in Example 1 and 0.36g of solid electrolyte A obtained in the same manner as in Example 1 were put into a 45mL zirconia can with 10 zirconia balls having a diameter of 10mm and sealed. Using a planetary ball mill device (manufactured by FRITSCH, model P-7), a rotation speed of 370rpm was used to mix for 20 hours at room temperature to obtain a positive electrode composite material powder. The obtained positive electrode composite material powder was subjected to the same measurement and test as in Example 5 (except for SEM-EDS measurement).

[0249] Table 4 shows the above results.

[0250] [Table 4]

[0251]

[0252] (Example 7)

[0253] 1. Preparation of positive electrode composite materials

[0254] (1) Preparation of solid electrolyte C

[0255] In the same manner as in Example 5, a solid electrolyte C was obtained.

[0256] (2) Preparation of positive electrode composite material powder

[0257] 1st Mixing Step

[0258] 0.7778 g of composite powder A and 0.2222 g of solid electrolyte A were put into a 45 mL zirconia can together with 10 zirconia balls with a diameter of 10 mm, and sealed. A planetary ball mill (Fritsch, model P-7) was used to mix at a speed of 370 rpm at room temperature for 20 hours to obtain composite powder G.

[0259] Second mixing step

[0260] 0.81 g of composite powder G and 0.09 g of solid electrolyte C were put into a 45 mL zirconia can together with 34 g of zirconia balls with a diameter of 2 mm, and sealed. A rolling mill ("small ball mill stand", manufactured by Asahi Rika Seisakusho, model AV-1) was used to mix at a speed of 600 rpm for 1 hour at room temperature to obtain a positive electrode composite material powder.

[0261] 2. Measurement methods and test methods

[0262] (1) Energy dispersive X-ray spectroscopy (SEM-EDS analysis) of electron microscope images and calculation of the overlap ratio of carbon and phosphorus

[0263] SEM-EDS analysis was performed in the same manner as in Example 1, and the overlap ratio was calculated.

[0264] (2) Powder X-ray Diffraction (XRD) of Positive Electrode Composite Material Powder

[0265] XRD measurement was carried out in the same manner as in Example 1, and the half width of the diffraction peak B was calculated.

[0266] (3) Weight reduction rate measurement test during heating

[0267] The same test as in Example 1 was carried out.

[0268] (4) Evaluation of battery characteristics

[0269] Preparation of negative electrode composite materials

[0270] A LTO negative electrode composite material was obtained in the same manner as in Example 5.

[0271] Fabrication of Lithium-ion Batteries (All-solid)

[0272] 100 mg of solid electrolyte A prepared by the above steps was pressurized in a cylinder made of MACOR (glass ceramic) with a diameter of 10 mm. The positive electrode composite material powder prepared above was put into the pressurized surface in a manner of 5.88 mg of sulfur, and pressurized again. 166 mg of LTO negative electrode composite material was put into the pressurized surface opposite to the positive electrode composite material and pressurized. A Li foil with a diameter of 9 mm and a thickness of 0.1 mm was put on it and pressurized again to make a full solid battery.

[0273] The obtained all-solid-state battery was subjected to a constant current charge and discharge test. The voltage range of the constant current charge and discharge test was set to -0.4 to +1.3 V, and the current value was set to the conditions in Table 5 below. As the discharge capacity (per sulfur mass) at 1 / 3C, the value of the 6th cycle under the following conditions was measured.

[0274] [Table 5]

[0275]

[0276] (Comparative Example 4)

[0277] 0.63g of composite powder A obtained in the same manner as in Example 1 and 0.27g of solid electrolyte A obtained in the same manner as in Example 1 were put into a 45mL zirconia can together with 10 zirconia balls having a diameter of 10mm, and sealed. Using a planetary ball mill device (manufactured by FRITSCH, model P-7), a rotation speed of 370rpm was used to mix for 20 hours at room temperature to obtain a positive electrode composite material powder. The obtained positive electrode composite material powder was subjected to the same measurement and test as in Example 7 (except for SEM-EDS measurement).

[0278] The above results are shown in Table 6.

[0279] [Table 6]

[0280]

[0281] (evaluate)

[0282] In Examples 1 to 7, diffraction peaks A and B were confirmed, and the overlap rate of carbon and phosphorus was also maintained at a high level. This indicates that the mixing state is good and the crystallinity of the solid electrolyte is maintained. As a result, the capacity under high current value and high rate conditions (the capacity at 1C in Examples 1 to 4, the capacity at 0.5C in Examples 5 and 6, and the capacity at 1 / 3C in Example 7) is high, and has excellent rate characteristics.

[0283] Industrial Applicability

[0284] The positive electrode composite material of the present invention is preferably used as a positive electrode of a lithium ion battery. In addition, the lithium ion battery of the present invention can be preferably used, for example, in batteries used in information-related equipment or communication equipment such as personal computers, cameras and mobile phones, and vehicles such as electric cars.

[0285] The above-mentioned several embodiments and / or examples of the present invention have been described in detail, but it is easy for those skilled in the art to add many changes to these illustrative embodiments and / or examples without departing from the novel teachings and effects of the present invention. Therefore, these many changes are also included in the scope of the present invention.

[0286] The contents of all the documents described in this specification and the applications serving as the basis for the priority claim based on the Paris Convention of the present application are hereby cited.

Claims

1. A positive electrode composite material, characterized in that: Contains a conductive aid as a carbon material, a sulfur-based active material, and a solid electrolyte, In the elemental analysis using energy dispersive X-ray spectroscopy of electron microscope images, the overlap rate of carbon and phosphorus mapping is more than 50%. In powder X-ray diffraction using CuKα rays, the compound had a diffraction peak A at 2θ=20.2±0.5° and a diffraction peak B at 2θ=41.1±0.8°.

2. The positive electrode composite material according to claim 1, characterized in that The half width of the diffraction peak B is less than 1.15°.

3. The positive electrode composite material according to claim 1 or 2, characterized in that: The solid electrolyte includes lithium atoms, phosphorus atoms, sulfur atoms, bromine atoms, and iodine atoms.

4. The positive electrode composite material according to any one of claims 1 to 3, characterized in that: The weight reduction rate when heat-treated at 190° C. for 2 hours was 2.5% or more.

5. The positive electrode composite material according to any one of claims 1 to 4, characterized in that: The weight reduction rate of the sulfur-based active material when heat-treated at 190° C. for 2 hours was 7.0% or more.

6. The positive electrode composite material according to any one of claims 1 to 5, characterized in that: The invention is obtained by a manufacturing method including a first mixing step and a second mixing step, wherein the first mixing step is to obtain a first mixture by adding a solid electrolyte to a sulfur-based active material and mixing the mixture, and the second mixing step is to obtain a second mixture by further adding a solid electrolyte to the first mixture and mixing the mixture, and the mixing is performed with less energy than that in the first mixing step.

7. The positive electrode composite material according to claim 6, characterized in that: The first mixing step is to perform mixing treatment under conditions that promote amorphization of the solid electrolyte added in the first mixing step; The second mixing step is performed under the condition that the crystallinity of the solid electrolyte added in the second mixing step does not disappear.

8. A method for producing a positive electrode composite material, characterized in that: include: a first mixing step of adding a solid electrolyte to a sulfur-based active material and mixing the mixture to obtain a first mixture; and a second mixing step of further adding a solid electrolyte to the first mixture and mixing the mixture to obtain a second mixture; In the second mixing step, mixing is performed with less energy than in the first mixing step.

9. The method for producing a positive electrode composite material according to claim 8, characterized in that: The first mixing step is to perform mixing treatment under conditions that promote amorphization of the solid electrolyte added in the first mixing step; The second mixing step is performed under the condition that the crystallinity of the solid electrolyte added in the second mixing step does not disappear.

10. The method for producing a positive electrode composite material according to claim 8 or 9, characterized in that: A positive electrode composite material according to any one of claims 1 to 7 is produced.

11. A lithium ion battery, characterized in that: A positive electrode composite material comprising the positive electrode composite material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Solid sulfide electrolyte material, solid-state lithium battery, and method for manufacturing solid sulfide electrolyte material

    JP2013016423A

  • Positive electrode mixture including crystalline component

    JP2013258079A